Modelling the formation of two stellar generations in massive star clusters: the case of 30 Doradus - Domínguez Figueroa, Raúl Esteban; Pellegrini, Eric William; Klessen, Ralf S.; Rahner, Daniel (Monthly notices of the Royal Astronomical Society, 2023)
We study the evolution of embedded star clusters with the goal to reproduce 30 Doradus, specifically the compact star cluster known as R136 and its surrounding stellar envelope, which is believed to be part of an earlier star formation event. We employ the high-precision stellar dynamics code Nbody6+ + GPU to calculate the dynamics of the stars embedded in different evolving molecular clouds modelled with the 1D cloud/clusters code warpfield. We explore clouds with initial masses of Mcloud = 3.16 × 105 M⊙ that (re)-collapse allowing for the birth of a second generation. We explore different star formation efficiencies to find the best set of parameters that can reproduce the observations. Our best-fit models correspond to a first generation of stars with a total mass M in the range $1.26 \!-\! 2.85× \,\,10^4\,$ M⊙. As the initial stellar feedback is insufficient to unbind the parental cloud, the gas re-collapses after about 2-4 million years and builds up a second generation of stars with M ≈ 6.32 × 104 M⊙. We can match the observed stellar ages, the radius of the shell of swept up cloud material, and the fact that the second generation of stars is more concentrated than the first one. This is independent of the cluster starting out with mass segregation or without. By comparing with recent measurements of mass segregation and density profile in the central region of the cluster we again find close agreement, providing further evidence for a re-collapse scenario building up multiple generations of stars in 30 Doradus.